SPRING SUGARCANE: A PROMISING CROP in subtropical India - Singh, D K; Kumar, Sanjay; Kumar, Purushottam; Rathi, A S (Indian Farming, 2015)
In spring sugarcane better yield and returns can be expected by selecting suitable varieties, which have the capacity for better germination and tillering. Planting of pre-sprouted setts enhances the germination of spring crop of sugarcane. Higher seed rate for planting, deeper planting depth and one pre-planting irrigation would result in better plant stand and productivity of spring sugarcane.